Dysbiosis of vaginal and cervical microbiome is associated with uterine fibroids - Mao, Xuetao; Chen, Hao; Peng, Xuan; Zhao, Xingping; Yu, Zheng; Xu, Dabao (Frontiers in Cellular and Infection Microbiology, 2023)
Dysbiosis of the female reproductive tract is closely associated with gynecologic diseases. Here, we aim to explore the association between dysbiosis in the genital tract and uterine fibroids (UFs) to further provide new insights into UFs etiology. We present an observational study to profile vaginal and cervical microbiome from 29 women with UFs and 38 healthy women, and 125 samples were obtained and sequenced. By comparing the microbial profiles between different parts of the reproductive tract, there is no significant difference in microbial diversity between healthy subjects and UFs patients. However, alpha diversity of UFs patients was negatively correlated with the number of fibroids. Increased Firmicutes were observed in both the cervical and vaginal microbiome of UFs patients at the phylum level. In differential analysis of relative abundance, some genera were shown to be significantly enriched (e.g., Erysipelatoclostridium, Mucispirillum, and Finegoldia) and depleted (e.g., Erysipelotrichaceae UCG-003 and Sporolactobacillus) in UFs patients. Furthermore, the microbial co-occurrence networks of UFs patients showed lower connectivity and complexity, suggesting reduced interactions and stability of the cervical and vaginal microbiota in UFs patients. In summary, our findings revealed the perturbation of microbiome in the presence of UFs and a distinct pattern of characteristic vaginal and cervical microbiome involved in UFs, offering new options to further improve prevention and management strategies.